Exogenous female sex steroid hormones and risk of asthma and asthma-like symptoms: a cross sectional study of the general population. Issue 8 (1st August 2001) - Lange, P; Parner, J; Prescott, E; Ulrik, C Suppli; Vestbo, J
Abstract : BACKGROUND: Recent evidence suggests a role for hormonal factors in the aetiology of asthma. METHODS: Data from a large study of women selected from the general population were used to relate treatment with oral hormonal contraceptives (OCP) and postmenopausal hormone replacement therapy (HRT) to the following asthma indicators: self-reported asthma, wheezing, cough at exertion, and use of medication for asthma. The study sample comprised 1536 premenopausal and 3016 postmenopausal women who participated in the third round of the Copenhagen City Heart Study in 1991–4. A total of 377 women were taking OCP (24.5% of premenopausal women) and 458 were on HRT (15.2% of postmenopausal women). RESULTS: In premenopausal women 4.8% reported having asthma. The prevalence of self-reported asthma, wheeze, use of asthma medication, and cough at exertion was not significantly related to use of OCP. In postmenopausal women the prevalence of self-reported asthma was 6.2%. A weak but consistent association was observed between HRT and self-reported asthma (OR 1.42 (95% CI 0.95 to 2.12)), wheeze (OR 1.29 (95% CI 1.02 to 1.64)), cough at exertion (OR 1.34 (95% CI 1.01 to 1.77)), and use of asthma medication (OR 1.45 (95% CI 0.97 to 2.18)). CONCLUSIONS: In this study of the general population no relationship was found between the use of OCP and asthma. Although an association was observed between HRT and asthma and asthma-like symptoms, this was relatively weak and it is concluded that there is no necessity to change present prescription practice.